PENGARUH IPM, RLS, TPT, DAN PENGELUARAN PERKAPITA TERHADAP KEMISKINAN DI PROVINSI JAWA BARAT - Ida Syafa'atur Rohmah; Jalu Aji Prakoso (Transpublika Publisher, 2022)
This study seeks to determine the influence of Human Development Index (HDI), Average Length of Schooling, Open Unemployment Rate, and Per capita Expenditures have on poverty in Cities in West Java Province during 2010 – 2020. This study uses a random effect model which is selected from three panel data processing methods through testing. The results showed that the HDI variables, the average length of schooling, the open unemployment rate and per capita expenditure together had an effect on the variation in the rise/fall of poverty. Simultaneously, the HDI variables, the average length of schooling, the open unemployment rate and per capita expenditure have a significant effect on poverty. Partially, the HDI variable and the average length of schooling have a significant effect on poverty. Meanwhile, the variables of the open unemployment rate and per capita expenditure have no significant effect on poverty.